Hemoglobinuria and acute kidney injury in severe malaria: Case reports from Borgou/Alibori Teaching Hospital, Benin - Seraphin Ahoui; Nonvignon Éric Ayadji; Giovanna Zossoungbo; Joseph Godonou; Aubin Melikan; Aimé Vinasse; Sabrina Conchita Somakou; Nicanor Houeto; Evariste Eteka; Jacques Vigan (Український Журнал Нефрології та Діалізу)
The hemoglobinuric form of severe malaria can precipitate acute kidney injury (AKI) and potential multiorgan failure. This report discusses two cases of fatal AKI due to severe malaria, treated in 2024 at the Borgou-Alibori Departmental Teaching Hospital in Benin. It examines the pathophysiology, clinical symptoms, and treatments used, providing detailed insights into the progression of the disease and the therapeutic interventions attempted. Key takeaways highlight the importance of early, multidisciplinary care in improving outcomes, with hemodialysis playing a critical role in managing AKI caused by hemoglobinuria.